Spatial knowledge, language, and cognitive adaptation to landscape among Siberian Ewenki - Mamontova, N (2020)
This thesis examines the relationships between spatial knowledge, adaptation, and mobility through the analysis of landscape terminology and place names among Ewenki, one of the hunting and reindeer herding Indigenous communities of Siberia. Ewenki have the biggest area of distribution in Eurasia among hunter-gatherers. It studies how this knowledge is linked to and reflected in people’s patterns and understanding of mobility, the ontology of geospatial domain, and cognitive adaptation to new environments in a broader cultural and geographic portrayal of the interactions between humans, animals, spirits, particular places, and landscapes. This thesis argues that mobility, which is linked to the precise knowledge of hydrological systems, has played a key role in spreading the system of landscape terminology and Ewenki place names over a huge territory of Siberia. Mobility is considered not only as the physical movement of people but also includes an understanding of landscape perception from a mobility perspective. This perspective corresponds to Ewenki’s understanding of the landscape as constantly changing or fluid. In contrast to sedentarist communities, Ewenki tend to perceive landscape objects as primarily fluid and their geospatial categories demonstrate a great deal of variation in meaning across communities.